High-density SNP-based genetic maps for the parents of an outcrossed and a selfed tetraploid garden rose cross, inferred from admixed progeny using the 68k rose SNP array - Vukosavljev, Mirjana; Arens, Paul; Voorrips, Roeland E; van ‘t Westende, Wendy PC; Esselink, GD; Bourke, Peter M; Cox, Peter; van de Weg, W Eric; Visser, Richard GF; Maliepaard, Chris; Smulders, Marinus JM (Horticulture research, 2016)
Dense genetic maps create a base for QTL analysis of important traits and future implementation of marker-assisted breeding. In tetraploid rose, the existing linkage maps include <300 markers to cover 28 linkage groups (4 homologous sets of 7 chromosomes). Here we used the 68k WagRhSNP Axiom single-nucleotide polymorphism (SNP) array for rose, in combination with SNP dosage calling at the tetraploid level, to genotype offspring from the garden rose cultivar ‘Red New Dawn’. The offspring proved to be not from a single bi-parental cross. In rose breeding, crosses with unintended parents occur regularly. We developed a strategy to separate progeny into putative populations, even while one of the parents was unknown, using principle component analysis on pairwise genetic distances based on sets of selected SNP markers that were homozygous, and therefore uninformative for one parent. One of the inferred populations was consistent with self-fertilization of ‘Red New Dawn’. Subsequently, linkage maps were generated for a bi-parental and a self-pollinated population with ‘Red New Dawn’ as the common maternal parent. The densest map, for the selfed parent, had 1929 SNP markers on 25 linkage groups, covering 1765.5 cM at an average marker distance of 0.9 cM. Synteny with the strawberry ( Fragaria vesca ) genome was extensive. Rose ICM1 corresponded to F. vesca pseudochromosome 7 (Fv7), ICM4 to Fv4, ICM5 to Fv3, ICM6 to Fv2 and ICM7 to Fv5. Rose ICM2 corresponded to parts of F. vesca pseudochromosomes 1 and 6, whereas ICM3 is syntenic to the remainder of Fv6. Genomics: Unravelling a rosy riddle The rose genome has been mapped in greater detail than ever, and a new method to determine hybrid plants' parentage developed. A Dutch team, led by Rene Smulders of Wageningen University, planned to cross two roses, 'Morden Centennial' and 'Red New Dawn,' and map the resulting hybrid's genome. However, the crossed population displayed unexpected traits. Using genetic differences at DNA sites known as 'single nucleotide polymorphisms,' the team determined the heritage of this population. They found not only crosses of 'Morden Centennial' and 'Red New Dawn', but also 'Red New Dawn' with an unknown parent, and self-fertilized 'Red New Dawn'. This evidence for self-fertilization in roses presents both challenges and opportunities for breeders. The team generated three genetic maps, the most detailed for the self-fertilized plants, supporting further genomic analysis and cultivar development in roses.